2012
DOI: 10.1136/bcr-2012-006676
|View full text |Cite
|
Sign up to set email alerts
|

Thigh haematoma following acupuncture treatment in a patient on warfarin

Abstract: A 82-year-old woman on warfarin for atrial-fibrillation was admitted via the acute medical take having developed a large haematoma in the right thigh (picture). She gave a history of recent acupuncture treatment for trochanteric bursitis. Acupuncture treatment had been given in the community and we do not know if the therapist was aware of the fact she was being treated with warfarin, nor do we know if enquiry was made about the state of anticoagulant control at the time of needle insertion. Retrospective exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…However, there are some articles that report AEs, such as bleeding from the inferior epigastric artery, 22 acute spinal subdural hematomas, 23 and hematomas on the buttocks. 24 Therefore, acupuncturists should avoid unnecessary deep needling and crude procedures regardless of their patients' bleeding tendencies.…”
Section: Assessment Of Each Adverse Eventmentioning
confidence: 99%
“…However, there are some articles that report AEs, such as bleeding from the inferior epigastric artery, 22 acute spinal subdural hematomas, 23 and hematomas on the buttocks. 24 Therefore, acupuncturists should avoid unnecessary deep needling and crude procedures regardless of their patients' bleeding tendencies.…”
Section: Assessment Of Each Adverse Eventmentioning
confidence: 99%
“…Moreover, some doctors prohibit their patients from receiving acupuncture during anticoagulant therapy, possibly because of the reported side effects. For example, Kenz et al 8 reported thigh hematoma after the acupuncture treatment of an 82-year-old woman taking warfarin. Her PT INR was 2.4 at the time of acupuncture treatment.…”
Section: Commentarymentioning
confidence: 99%
“…침치료 이상반응의 대부분이 미세출혈, 혈종 등 출혈과 관련된 이상반응이지만 출혈 고위험군인 항응고제, 항혈전 제 복용군에 대한 침치료 안전성 연구는 활발하게 이루어 지지 못했다. Kenz et al 6) 이 warfarin을 복용하는 환자에 서 침치료 후 발생한 중증의 혈종을 보고한 환자 사례 보고 이후, Miller et al 7) 의 후향적 환자-대조군 연구, 최근 Kim et al 8) 의 후향적 차트 리뷰가 현재까지 이루어진 연구 이다. 이와는 대조적으로 침치료와 비슷하게 검사 과정 중 needling이 시행되는 근전도 검사 같은 경우 Mayo clinic 을 필두로 Lynch et al 9) 의 연구, Gertken et al 10) 의 연구, Boon et al 11) 의 연구 등 초음파 진단기기나 magnetic resonance imaging(MRI)기기 등을 이용한 비교적 대규모 전향적 연구가 진행되었으며, 결과적으로 항응고제나 항혈 전제를 복용하는 환자에게도 근전도 검사가 안전함을 증명 하였다.…”
Section: ⅰ 서 론unclassified